Coping and Stress Management Training as an Effort to Improve Stress Adaption Ability - Zakiyah, Ana; Rofi'ah, Ika Ainur (Poltekkes Kemenkes Tanjung Karang, 2023)
Each interacts with the environment and gives a different response, namely a positive response and even a negative response because he considers that changing conditions is a pressure that causes stress and encourages individuals to respond to coping. The research objective was to determine the effectiveness of coping and stress management training in increasing the perception of stress in health levels before and after the intervention was given. The design used one group pre-post design. The population was 30 health cadres, and the sampling technique used total sampling. Before the activity, the respondents were given a questionnaire to determine stress levels, followed by training. The respondents applied stress management techniques within one month, after which a post-test was carried out. The instrument used the Perceived Stress Scale. The results showed that the mean stress adaptation of respondents before the intervention was 20.73, and the mean stress adaptation after the intervention was 7.83. Further analysis using a paired t-test showed a significant difference in stress adaptation between stress adaptations to health cadres before and after the intervention (p-value=0.001; Î±